Membrane-free asymmetric Faraday capacitive deionization device and application

By developing a membrane-free asymmetric Faraday capacitor deionization device, using nitrogen-doped porous carbon-coated nanobismuth materials and oxygen-rich transition metal carbide materials, the problems of low charging efficiency and insufficient electrode material capacity in high-concentration salt solutions are solved, and efficient seawater desalination is achieved and the application concentration range is broadened.

CN119833318AActive Publication Date: 2025-04-15ZHEJIANG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510035482.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

Traditional CDI devices have low charging efficiency when dealing with high concentration salt solutions, and the common ion discharge effect is severe, resulting in the inability to perform desalination normally. The low capacity and short cycle times of the electrode material limit their application range.

Method used

A membrane-free asymmetric Faraday capacitor deionization device was developed, using nanobismuth material coated with nitrogen-doped porous carbon as the Faraday positive electrode, and an oxygen-rich transition metal carbide material as the Faraday negative electrode, which was directly assembled, avoiding the use of ion exchange membranes.

Benefits of technology

The device exhibits high adsorption capacity and excellent cycling performance in high salt concentration sodium chloride solution, and can perform desalination work stably and efficiently, broadening the concentration range for capacitor deionization applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833318A_ABST
    Figure CN119833318A_ABST
Patent Text Reader

Abstract

The device comprises a Faraday positive electrode and a Faraday negative electrode, the Faraday positive electrode comprises a nano bismuth material Bi (at) NCNF coated with nitrogen-doped porous carbon, and the Faraday negative electrode comprises a transition metal carbide material MX-O rich in oxygen functional groups. The device does not comprise an ion exchange membrane. The asymmetric Faraday capacitive deionization device provided by the invention is formed by directly assembling the positive electrode and the negative electrode, has high adsorption capacity and long cycle performance, effectively solves the problems of low capacity and low cycle index of a traditional capacitive deionization device, and expands the concentration range of desalination application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of capacitor deionization, and in particular to a membrane-free asymmetric Faraday capacitor deionization device and application thereof. Background Art

[0002] Capacitive deionization (CDI) is an emerging desalination technology that has attracted much attention in recent years. Unlike other desalination methods, CDI devices do not extract water from salt solutions, but adsorb ions dissolved in salt solutions on the double-layer region at the interface between electrodes and solutions to achieve separation. Unlike traditional desalination technologies that require precise membrane elements, high-pressure pumps or heat sources, CDI devices can operate at an applied voltage of less than 2V under mild conditions such as low osmotic pressure and room temperature. Compared with other desalination technologies, it has the advantages of low cost and environmental protection and energy saving. At the same time, the CDI device can selectively extract some ions in the solution, giving it a variety of potential application scenarios including seawater desalination, hard water softening, heavy metal salt purification, industrial, agricultural and household water decontamination, nuclear power plant wastewater treatment, and precious metal ion resource recovery.

[0003] The working parts of the CDI device are mainly composed of positive and negative electrodes, which adsorb anions and cations in the solution respectively. The adsorption performance is also directly related to the performance of the positive and negative electrodes and their matching. Limited by the low ion adsorption capacity of traditional carbon-based electrode materials, the practical application of CDI still faces many challenges. Taking seawater desalination as an example, as the salt concentration of the treated solution gradually increases, the negative impact of the common ion expulsion effect of carbon-based electrode materials will inevitably become more prominent, resulting in a sharp decrease in charging efficiency and even inability to perform desalination work normally. Therefore, traditional CDI can currently only treat extremely low concentrations of brackish water (<3000mg / L), and there is still a large gap from medium and high concentrations of brackish water (≥3000mg / L) and even actual concentrations of seawater (~35000mg / L). On the other hand, the low capacity performance of traditional carbon-based electrodes is also an important reason for the unsatisfactory adsorption of CDI devices. To date, various new electrodes developed in the field still have a lot of room for improvement. It is worth mentioning that although some CDI devices have further improved their application scope and performance by introducing additional ion exchange membranes, the expensive membrane elements will also become a new obstacle to their promotion. Therefore, the development and matching of new positive and negative electrode materials with high ion selectivity, high capacity and long cycle performance is crucial for the further development of membrane-free CDI.

[0004] In recent years, a faradaic deionization (FDI) based on battery materials has received widespread attention. Compared with the working principle of pure physical adsorption of carbon-based electrodes, faradaic electrodes have more types of reaction mechanisms, such as ion intercalation, redox, conversion reactions, etc. More types of reaction mechanisms give faradaic electrodes higher desalination performance and better ion selectivity, and eliminate the possibility of common ion expulsion effects from the working principle. However, to date, the development of most faradaic materials has been limited to negative electrode materials, that is, the removal of cations (especially sodium ions), while research on faradaic positive electrode materials for anions is relatively small. For example, a Chinese patent with publication number CN116959895A discloses a Prussian blue analog electrode used for hybrid capacitive deionization, in which the Prussian blue analog is a faradaic capacitor that adsorbs sodium ions, and activated carbon is used as a double-layer capacitor to adsorb chloride ions, thereby removing sodium chloride and achieving the purpose of desalination. And a Chinese patent with publication number CN113077996A discloses a preparation method and application of a sodium vanadium oxyfluorophosphate / graphene composite electrode material. The method is based on the principle of Faraday capacitance and double-layer capacitance to store charge. In a mobile electrode capacitor deionization device, under a certain voltage, one electrode uses a sodium vanadium oxyfluorophosphate / graphene composite mobile electrode slurry as a Faraday capacitor to adsorb sodium ions, and the other electrode uses activated carbon as a double-layer capacitor mobile electrode slurry to adsorb chloride ions, thereby removing sodium chloride and achieving the purpose of desalination.

[0005] On the other hand, the performance matching problem of the positive and negative electrode materials of FDI devices has not received enough attention. The common volume expansion problem of Faraday positive electrode materials is the culprit for the rapid decay of cycle performance, and the specific capacity of Faraday negative electrode materials themselves still has a lot of room for improvement, which seriously affects the further development of FDI.

[0006] Therefore, how to develop high-performance Faraday positive electrode materials and high-performance Faraday negative electrode materials separately and assemble them into an asymmetric system to form a new FDI device with both high adsorption capacity and long cycle performance is of great significance to the development and application of FDI and even CDI. Summary of the invention

[0007] The object of the present invention is to provide a membrane-free asymmetric Faraday capacitor deionization device, which has both high adsorption capacity and long cycle performance when applied to desalination, and expands the concentration range of desalination applications.

[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] A membrane-free asymmetric Faraday capacitor deionization device comprises a Faraday positive electrode and a Faraday negative electrode, wherein the Faraday positive electrode comprises a nitrogen-doped porous carbon-coated nano-bismuth material Bi@NCNF, and the Faraday negative electrode comprises a transition metal carbide material MX-O rich in oxygen functional groups, and the device does not comprise an ion exchange membrane.

[0010] The membrane-free asymmetric Faraday capacitor deionization device provided by the present invention is directly assembled from the above-mentioned Faraday positive electrode and Faraday negative electrode without including any ion exchange membrane, and has both high adsorption capacity and long cycle performance, effectively solving the problems of low capacity and low cycle number existing in traditional capacitor deionization devices.

[0011] The preparation method of the nitrogen-doped porous carbon-coated nano-bismuth material Bi@NCNF comprises: using bismuth nitrate pentahydrate, pyrazole-3,5-dicarboxylic acid and camphoric acid as raw materials, hydrothermally reacting to obtain a precursor; and calcining the precursor to obtain Bi@NCNF.

[0012] The feed ratio of bismuth nitrate pentahydrate, pyrazole-3,5-dicarboxylic acid and camphoric acid is: 0.8 g of bismuth nitrate pentahydrate (purity ≥ 99.0%), 0.35 g of pyrazole-3,5-dicarboxylic acid (purity ≥ 99.0%), and 0.4 g of camphoric acid (purity ≥ 99.0%).

[0013] The temperature of the hydrothermal reaction is 120° C., and the reaction time is 96 hours.

[0014] The calcination temperature is 600-800°C.

[0015] Preferably, the calcination temperature is 600-700° C. The size and typical porous hollow morphology of the nano-bismuth in Bi@NCNF obtained under the calcination conditions are more conducive to improving the adsorption capacity of the assembled FDI device.

[0016] Preferably, the size of the nano-bismuth in the nitrogen-doped porous carbon-coated nano-bismuth material Bi@NCNF is 30 nm to 100 nm.

[0017] The Faraday positive electrode uses Bi@NCNF as an active material, which is ground and mixed with conductive carbon black and PVDF powder in N-methylpyrrolidone, sprayed on conductive carbon paper, and dried for use as a positive electrode.

[0018] The preparation method of the oxygen-rich transition metal carbide material MX-O comprises: mechanically mixing titanium aluminum carbide, hydrochloric acid and lithium fluoride to react and obtain a transition metal carbide suspension as a precursor material; and subjecting the precursor material to room temperature plasma discharge activation treatment in a hydrogen atmosphere to obtain a transition metal carbide suspension rich in oxygen functional groups.

[0019] The feed ratio of titanium aluminum carbide, hydrochloric acid and lithium fluoride is: 1 gram of titanium aluminum carbide (purity ≥ 99.0%), 20 milliliters of hydrochloric acid (concentration 9.0 mol / L), and 1 gram of lithium fluoride (purity ≥ 99.0%).

[0020] In the plasma discharge activation treatment, the activation treatment time of 50 mg of the precursor material is 3-5 minutes.

[0021] Preferably, the processing time of the precursor material is 3-5 minutes, so that the assembled FDI device can have a higher sodium ion adsorption capacity.

[0022] Among them, a transition metal carbide suspension rich in oxygen functional groups is vacuum filtered into a thin film and directly used as a negative electrode.

[0023] The present invention also provides an application of the membrane-free asymmetric Faraday capacitor deionization device in desalination. The concentration of the sodium chloride solution is 2000-35000 mg / L.

[0024] Compared with the prior art, the present invention has the following advantages:

[0025] 1. The FDI device of the present invention broadens the concentration range of capacitive deionization for seawater desalination: for example, the device can still perform stable and efficient desalination in a high-salt concentration sodium chloride solution of 5000 mg / L, while the traditional CDI device is limited to the desalination of brackish water within a concentration of 3000 mg / L due to the influence of the common ion expulsion effect.

[0026] 2. The FDI device of the present invention has a high adsorption capacity: for example, when a constant charging voltage of 1.2 V is applied and the charging time is 60 minutes, a desalination test is performed in a sodium chloride solution with a concentration of 5000 mg / L, and an optimal high adsorption capacity of up to 70 mg / g can be obtained.

[0027] 3. The FDI device of the present invention has excellent cycle performance: for example, when a constant charging voltage of 1.2V and a constant discharging voltage of 1.2V are applied, and the total duration of a single adsorption-desorption cycle is 60 minutes, a continuous desalination test is carried out in a sodium chloride solution with a concentration of 5000 mg / L, and the capacity retention rate after 100 cycles is as high as 90.0%.

[0028] 4. The FDI device described in the present invention is simple to assemble and does not contain additional components such as ion exchange membranes. It is directly assembled from the above-mentioned positive electrode and negative electrode, and has the potential for further promotion and use in terms of cost and process. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1The transmission electron microscope (TEM) image of the nano-bismuth prepared in Example 1-3 shows a porous bismuth structure on the surface of the carbon nanobeams;

[0030] Figure 2 This is a high-resolution transmission electron microscopy (HRTEM) image of the porous carbon-coated nano-bismuth prepared in Example 1, in which two typical morphologies, a carbon coating layer and a hollow region, are observed;

[0031] Figure 3 This is an energy dispersive spectrometer (EDS) image of the nitrogen-doped porous carbon-coated nano-bismuth obtained in Example 1. It is observed that the nitrogen-doped porous carbon-coated nano-bismuth is composed of four elements: bismuth, carbon, nitrogen, and oxygen;

[0032] Figure 4 X-ray photoelectron spectroscopy (XPS) diagrams of transition metal carbides prepared in Examples 4-6 and Comparative Example 1 show changes in the content of oxygen functional groups in the transition metal carbides;

[0033] Figure 5 Electrochemical quartz crystal microbalance (EQCM) tests of the transition metal carbides prepared in Examples 4-6 and Comparative Example 1 demonstrated changes in the adsorption capacity of the transition metal carbides for sodium ions;

[0034] Figure 6 The cyclic voltammetry curve of the nano-bismuth prepared in Example 1-3 in a 1 mol / L sodium chloride solution system;

[0035] Figure 7 Cyclic voltammetry curves of the transition metal carbides prepared in Examples 4-6 and Comparative Example 1 in a 1 mol / L sodium chloride solution system;

[0036] Figure 8 A schematic diagram of a membrane-free asymmetric Faraday capacitor deionization device provided by the present invention;

[0037] Fig. 9 The adsorption capacity curve of the asymmetric FDI in the sodium chloride solution with a concentration of 5000 mg / L in each combination of Examples 1-3, Example 4 and Comparative Example 1;

[0038] Fig.10 The cycle performance of the asymmetric FDI in a sodium chloride solution with a concentration of 5000 mg / L is shown in FIG. 1 and FIG. 4.

[0039] Fig.11 The adsorption capacity curves of the asymmetric FDI devices assembled in Example 1 and Example 4 in sodium chloride solutions of different concentrations. DETAILED DESCRIPTION

[0040] Example 1: 0.8 g of bismuth nitrate pentahydrate (purity ≥ 99.0%), 0.35 g of pyrazole-3,5-dicarboxylic acid (purity ≥ 99.0%), 0.4 g of camphor acid (purity ≥ 99.0%), 10 ml of deionized water, 10 ml of N-methylpyrrolidone (purity ≥ 99.0%), and 10 ml of acetamide (purity ≥ 99.0%) were mechanically mixed and reacted in a hydrothermal kettle at a temperature of 120°C for 96 hours. The precursor material prepared by the above reaction was washed several times by centrifugation with ethanol, and after being fully dried, it was heated at a temperature of 700°C for 2 hours in an argon atmosphere, and after cooling to room temperature, a nitrogen-doped porous carbon-coated nano-bismuth electrode material was obtained. Nano-bismuth is used as an active material, ground and mixed with conductive carbon black (purity ≥ 99.0%) and PVDF powder (purity ≥ 99.0%) in N-methylpyrrolidone in a mass ratio of 8:1:1, and finally sprayed onto conductive carbon paper and dried for use as a positive electrode, namely Bi@NCNF-700.

[0041] Example 2: The difference from Example 1 is that when preparing the nitrogen-doped porous carbon-coated nano-bismuth electrode material, the heating temperature under the argon atmosphere is changed from 700° C. to 600° C. to obtain the positive electrode, namely Bi@NCNF-600.

[0042] Example 3: The difference from Example 1 is that when preparing the nitrogen-doped porous carbon-coated nano-bismuth electrode material, the heating temperature under the argon atmosphere is changed from 700° C. to 800° C. to obtain the positive electrode, namely Bi@NCNF-800.

[0043] The electrode material morphology obtained in Example 1-3 is a nitrogen-doped porous carbon-coated nano-bismuth material ( Figure 1 ).from Figure 1 It can be seen that the size and content of nano-bismuth in different embodiments are different: in Example 1, it can be observed that the nano-bismuth exhibits agglomeration characteristics, with large-sized nanoparticles (large size greater than or equal to 100 nm) and a high bismuth content; in Example 2, it can be observed that the nano-bismuth exhibits uniform dispersion characteristics, the nanoparticle size is reduced, and the spherical characteristic morphology of the nano-bismuth can be clearly observed (the medium size is between 30nm and 100nm, and the nano-bismuth is evenly dispersed), and the material still has a high bismuth content; in Example 3, it can be observed that the content of nano-bismuth decreases sharply, and only a small amount of nano-bismuth with a smaller size (small size less than or equal to 30nm) exists.

[0044] The nano-bismuth material obtained in Example 1 has a typical porous carbon-coated morphology ( Figure 2 ).from Figure 2 It can be seen that there is a stacked carbon coating around the nano-bismuth, which is beneficial to electron transmission and enhances the conductivity and structural stability of the nano-bismuth material; Figure 2It can be seen that there are porous hollow areas between the carbon coating layers, which is conducive to ion storage and increases the specific surface area and ductility of the nano-bismuth material.

[0045] The nano-bismuth material obtained in Example 1 is composed of multiple elements such as bismuth, carbon, nitrogen, and oxygen ( Figure 3 ).from Figure 3 It can be seen that the bismuth element is distributed in a spherical shape, proving that bismuth exists in the form of nanoparticles; carbon, nitrogen and oxygen elements are evenly distributed, proving that the material coating the nano-bismuth is nitrogen-doped porous carbon.

[0046] Example 4: 1 gram of titanium carbide (purity ≥ 99.0%), 20 milliliters of hydrochloric acid (concentration 9.0 mol / L), and 1 gram of lithium fluoride (purity ≥ 99.0%) are mechanically mixed and stirred continuously for 24 hours at a temperature of 35°C, and then centrifuged with deionized water for multiple times until the pH value of the solution is close to 5. First, ultrasonicate for 1 hour under ice bath conditions, and then centrifuge at a speed of 3500 rpm for 1 hour to obtain a transition metal carbide suspension. The precursor material prepared by the above reaction is subjected to room temperature plasma discharge activation treatment at a voltage of 50V under a hydrogen atmosphere. The activation treatment time for 5 minutes is 50 mg of the precursor material (10 milliliters of a precursor solution with a concentration of 5 mg / ml), and a transition metal carbide suspension rich in oxygen functional groups can be obtained. Finally, the suspension is vacuum filtered into a thin film and directly used as a negative electrode, i.e., MX-O2.

[0047] Comparative Example 1: The difference from Example 4 is that when preparing the transition metal carbide rich in oxygen functional groups, the plasma discharge activation time is changed from 5 min to 0 min to obtain a negative electrode, namely, Pristine MX.

[0048] Example 5: The difference from Example 4 is that when preparing the transition metal carbide rich in oxygen functional groups, the plasma discharge activation time is changed from 5 min to 3 min to obtain the negative electrode, namely, MX-O1.

[0049] Example 6: The difference from Example 4 is that when preparing the transition metal carbide rich in oxygen functional groups, the plasma discharge activation time is changed from 5 min to 10 min to obtain the negative electrode, namely, MX-O3.

[0050] The electrode materials obtained in Examples 4-6 and Comparative Example 1 are transition metal carbide materials ( Figure 4 ).from Figure 4 It can be seen that the oxygen functional groups (C-Ti-O x ) and hydroxyl functional groups (C-Ti-(OH) x) content and conversion relationship: Comparative Example 1 has the highest hydroxyl functional group (C-Ti-(OH) x ) content (i.e. 34.3%) and the relatively lowest oxygen functional group (C-Ti-O x ) content (i.e. 11.8%), the hydroxyl functional groups (C-Ti-(OH) x ) content gradually decreases, oxygen functional groups (C-Ti-O x ) content gradually increased, proving that with the increase of discharge activation time, the hydroxyl functional group (C-Ti-(OH) x ) will gradually transform into oxygen functional groups (C-Ti-O x ), the lowest hydroxyl functional group (C-Ti-(OH) x ) content (i.e. 18.3%) and the highest oxygen functional group (C-Ti-O x ) content (i.e. 27.7%).

[0051] The electrode materials obtained in Examples 4-6 and Comparative Example 1 are transition metal carbide materials ( Figure 5 ).from Figure 5 It can be seen that the adsorption capacity of the transition metal carbide materials of Examples 4-6 and Comparative Example 1 for sodium ions during charging is compared: under the same charging charge, Example 4 has the relatively highest sodium ion adsorption mass (that is, when the total charging charge is -0.3mC, the sodium ion adsorption mass is 158.1ng), the sodium ion adsorption mass of Example 5 is slightly reduced (that is, when the total charging charge is -0.3mC, the sodium ion adsorption mass is 93.3ng), and the sodium ion adsorption mass of Example 6 is slightly reduced (that is, when the total charging charge is -0.3mC, the sodium ion adsorption mass is 77.9ng), and Comparative Example 1 has the relatively lowest sodium ion adsorption mass (that is, when the total charging charge is -0.3mC, the sodium ion adsorption mass is 51.7ng).

[0052] 1. Electrochemical performance test of positive and negative electrodes:

[0053] The AutoLAB electrochemical workstation was used to perform cyclic voltammetry tests of a three-electrode system (reference electrode silver / silver chloride, counter electrode platinum sheet), and the electrolyte was 1 mol / L sodium chloride solution. The voltage window for nano-bismuth electrode materials was -1.2 to 0.8 V, and the scan rate was set to 5 mV / s; the voltage window for transition metal carbide electrode materials was -1 to 0 V, and the scan rate was set to 5 mV / s.

[0054] Figure 6 The cyclic voltammetry curve of the nitrogen-doped porous carbon-coated nano-bismuth electrode material prepared in Example 1-3 in a 1 mol / L sodium chloride solution system; Figure 6It can be seen that Examples 1-3 all have typical oxidation peak and reduction peak characteristics of bismuth materials. The cyclic voltammetry curve area of ​​Example 1 is larger than that of Examples 2-3, that is, the electrochemical performance of Bi@NCNF-700 is greater than that of Bi@NCNF-600 and Bi@NCNF-800 (the specific capacities of Examples 1-3 are specifically 398F / g, 262F / g, and 152F / g, that is, the performance of Example 1 is better than that of Example 2 and Example 3).

[0055] Figure 7 The cyclic voltammetry curves of the transition metal carbides prepared in Examples 4-6 and Comparative Example 1 in a 1 mol / L sodium chloride solution system are shown in FIG. Figure 7 It can be seen that Examples 4-6 and Comparative Example 1 all exhibit typical pseudocapacitive shape characteristics. The cyclic voltammetry curve area of ​​Example 4 is larger than that of Examples 5-6 and Comparative Example 1, that is, the electrochemical performance of MX-O2 is greater than that of MX-O1, MX-O3 and Pristine MX (the specific capacities of Examples 4-6 and Comparative Example 1 are specifically 63.7F / g, 59.4F / g, 49.6F / g, and 26.6F / g, that is, the performance of Example 4 is better than that of Example 6, Example 5, and Comparative Example 1).

[0056] 2. Test of electrosorption performance of asymmetric FDI:

[0057] In order to test the adsorption effect of the present invention on brackish water desalination, the embodiments were assembled into different systems of membrane-free asymmetric FDI to carry out corresponding adsorption performance test experiments ( Figure 8 ):

[0058] System 1: Example 1 and Example 4 were assembled into an asymmetric FDI device, and desalination test was carried out in a sodium chloride solution with a concentration of 5000 mg / L. The charging condition was constant voltage 1.2V, charging for 30 minutes, and the discharging condition was constant voltage -1.2V, discharging for 30 minutes ( Fig. 9 ), long cycle performance test is to test 100 cycles continuously ( Fig.10 ).

[0059] System 2: Example 2 and Example 4 were assembled into an asymmetric FDI device, and desalination test was carried out in a sodium chloride solution with a concentration of 5000 mg / L. The charging condition was constant voltage 1.2V, charging for 30 minutes, and the discharging condition was constant voltage -1.2V, discharging for 30 minutes ( Fig. 9 ).

[0060] System 3: Example 3 and Example 4 were assembled into an asymmetric FDI device, and desalination test was carried out in a sodium chloride solution with a concentration of 5000 mg / L. The charging condition was constant voltage 1.2V, charging for 30 minutes, and the discharging condition was constant voltage -1.2V, discharging for 30 minutes ( Fig. 9 ).

[0061] System 4: Example 1 and Comparative Example 1 were assembled into an asymmetric FDI device, and desalination tests were performed in a sodium chloride solution with a concentration of 5000 mg / L. The charging conditions were constant voltage 1.2 V and charging for 30 minutes, and the discharging conditions were constant voltage -1.2 V and discharging for 30 minutes ( Fig. 9 ).

[0062] from Fig. 9 It can be seen that the asymmetric FDI under different systems has different adsorption properties. The adsorption amounts measured in systems 1 to 4 are 71.7 mg / g, 50.9 mg / g, 41.3 mg / g, and 55.2 mg / g, respectively. That is, system 1 is better than system 4, better than system 2, and better than system 3. That is, in system 1, Example 1 and Example 4 are assembled into an asymmetric FDI device, which has the best desalination adsorption performance.

[0063] from Fig.10 It can be seen that after the system 1 was subjected to 100 consecutive long cycle performance tests, there was no obvious attenuation in the desalination adsorption performance, and the desalination adsorption performance of a single cycle was stably maintained at around 70 mg / g, proving that the system 1 in which Example 1 and Example 4 were assembled into an asymmetric FDI device had good cycle performance.

[0064] 3. Example 1 and Example 4 were assembled into an asymmetric FDI device, and desalination tests were performed in sodium chloride solutions with concentrations of 35000 mg / L, 20000 mg / L, 10000 mg / L, 5000 mg / L and 2000 mg / L, respectively. The charging conditions were constant voltage 1.2 V and charging for 30 minutes, and the discharging conditions were constant voltage -1.2 V and discharging for 30 minutes ( Fig.11 ), the measured adsorption amounts were 124.74 mg / g, 114.31 mg / g, 90.70 mg / g, 71.74 mg / g and 37.82 mg / g respectively.

Claims

1. A membrane-free asymmetric Faraday capacitor deionization device, characterized in that: The device comprises a Faraday positive electrode and a Faraday negative electrode, wherein the Faraday positive electrode comprises a nitrogen-doped porous carbon-coated nano-bismuth material Bi@NCNF, and the Faraday negative electrode comprises a transition metal carbide material MX-O rich in oxygen functional groups, and the device does not comprise an ion exchange membrane.

2. The membrane-free asymmetric Faraday capacitor deionization device according to claim 1, characterized in that: The preparation method of the nitrogen-doped porous carbon-coated nano-bismuth material Bi@NCNF comprises: using bismuth nitrate pentahydrate, pyrazole-3,5-dicarboxylic acid and camphoric acid as raw materials, hydrothermally reacting to obtain a precursor; and calcining the precursor to obtain Bi@NCNF.

3. The membrane-free asymmetric Faraday capacitor deionization device according to claim 2, characterized in that: The calcination temperature is 600-800°C.

4. The membrane-free asymmetric Faraday capacitor deionization device according to claim 1, characterized in that: In the Faraday positive electrode, Bi@NCNF is used as an active material, which is ground and mixed with conductive carbon black and PVDF powder in N-methylpyrrolidone, sprayed on conductive carbon paper, and dried for use as a positive electrode.

5. The membrane-free asymmetric Faraday capacitor deionization device according to claim 1, characterized in that: The preparation method of the transition metal carbide material MX-O rich in oxygen functional groups comprises: mechanically mixing titanium aluminum carbide, hydrochloric acid and lithium fluoride to react and obtain a transition metal carbide suspension as a precursor material; subjecting the precursor material to room temperature plasma discharge activation treatment under a hydrogen atmosphere to obtain a transition metal carbide suspension rich in oxygen functional groups; in the plasma discharge activation treatment, the activation treatment time is 3-10 minutes.

6. The asymmetric Faraday capacitor deionization device according to claim 5, characterized in that: In the plasma discharge activation treatment, the activation treatment time of 50 mg of the precursor material is 3-5 minutes.

7. The membrane-free asymmetric Faraday capacitor deionization device according to claim 6, characterized in that: The transition metal carbide suspension rich in oxygen functional groups is vacuum filtered into a thin film and directly used as a negative electrode.

8. The membrane-free asymmetric Faraday capacitor deionization device according to claim 1, characterized in that: The size of the nano-bismuth in the nitrogen-doped porous carbon-coated nano-bismuth material Bi@NCNF is 30 nm to 100 nm.

9. Use of the membraneless asymmetric Faraday capacitor deionization device according to any one of claims 1 to 8 in desalination.

10. The use according to claim 9, characterized in that: The desalting solution is a sodium chloride solution with a concentration of 2000-35000 mg / L.

Citation Information

Patent Citations

  • Preparation method and application of sodium vanadium oxyfluorophosphate / graphene composite electrode material

    CN113077996A

  • Preparation method and application of Prussian blue analogue electrode applied to hybrid capacitive deionization

    CN116959895A

  • CDI electrode active material and preparation and application thereof

    CN115626692A

  • Preparation method of room-temperature plasma activated MXene electrode material and product and application of room-temperature plasma activated MXene electrode material

    CN117153568A